Prospects for the introduction of Ferula tadshikorum Pimenov in the conditions of the Tashkent region - Khamraeva, Dilovar T.; Khojimatov, Olim; Bussmann, Rainer W.; Khujanov, Alisher; Kosimov, Zokir (Ethnobotany Research and Applications, 2022)
Background: Ferula species are used for a wide variety of purposes from the Middle East to the Himalayas. This paper provides information on the biological features and ontogenesis of the promising medicinal plant Ferula tadshikorum Pimenov during the introduction in the conditions of the Tashkent Botanical Garden. Methods: The features of morphological development of the studied ontogenetic states were recorded during similar periods of vegetation in 2019-2021 in two variants of treatment. Under the conditions of introduction, 2 growth periods (latent, virginal) and 4 age classes (seedlings, juvenile, immature and virginal plants) were documented in plant ontogenesis. Results: According to our study, a rapid transition from one to the next age state was found in introduced specimens. This is an important factor for the establishment of agro-coenoses needed to obtain raw material in a significantly shorter time. The results of the study show the success of the introduction of Ferula tadshikorum in the conditions of the Tashkent Botanical Garden, although the new growth conditions differed from natural soil and climatic characteristics. The collection of this species in the Garden can now serve as a basis for plantations in natural growing conditions. Conclusion: The obtained experimental data can be used as a basis for the development of agricultural techniques and technologies for growing this plant in introduced conditions. Keywords. Ferula tadshikorum, introduction, root, medicinal plant, monocarpic, ontogenesis.